PERBEDAAN INTENSITAS NYERI MENSTRUASI SEBELUM DAN SESUDAH HERBAL THERAPY COMPRESS BALL PADA REMAJA PUTRI DI SMAN 2 TABANAN - Wulandari, Putu Pradnya; Suarniti, Ni Wayan; Utarini, Gusti Ayu Eka (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2024)
Dysmenorrhea occurs in 90% of Indonesian women, and 10% experience severe dysmenorrhea that interferes with daily activities. Dysmenorrhoea can be treated pharmacologically and non-pharmacologically. One non-pharmacological treatment is using herbal therapy compress balls. The aim of this research was to determine the difference in the intensity of menstrual pain before and after herbal compress ball therapy in class X-XI female students at SMA Negeri 2 Tabanan. The design of this research is pre-experimental with a one group pretest-posttest design. The sampling technique used Non Probability Sampling, Purposive Sampling type with a total of 20 respondents. The instrument used was the NRS (Numeric Rating Scale) pain scale measurement sheet. The results of the data normality test showed that the data was not normally distributed, so the analysis used the Wilcoxon test. The results of data analysis show that there is a difference before and after the Herbal Therapy Compress Ball with a value of p = 0.000 (? < 0.05). The level of menstrual pain among young women obtained from the lowest pretest score was four and the highest score was six, and the median value was five. Meanwhile, the posttest results showed that the lowest score was one and the highest score was three, and the median was two. So it proves that there is a significant difference in the intensity of menstrual pain in young women before and after being given the Herbal Therapy Compress Ball.